Oral ingestion of foreign body in neonates and infants: a clinical review - Sahoo, Loknath; Rath, Aditi Ava; Swain, Santosh Kumar; Das, Saumya Ranjan; Pani, Santosh Kumar; Baliarsingh, Prasenjit (International Journal of Contemporary Pediatrics, 2022)
Foreign body (FB) ingestion in adult and children population is not uncommon but accidental. Same is rare in neonates and infants. Many of the FBs ingestion go unnoticed or unexpressed if baby is preverbal. Most of the foreign bodies pass spontaneously per anal. Only the larger size or sharp FBs get stuck in places of gastro intestinal tract and presents the patient in emergency department. Similarly corrosive and toxic FBs also invite immediate attention. Literature on the clinical aspects of the foreign body ingestion among neonates and infants was searched electronically through PubMed and individual study. Relevant articles were reviewed thoroughly and summarized. Instances of foreign body ingestion (FBI) in neonate and adult are in ascending trend over last several years. Imaging and identification of radiolucent FBs become challenging for surgeons. Conservative treatment for spontaneous evacuation, endoscopic retrieval and surgical removal are the modalities for FBI management.